Boron-Nitrogen-Co-Doping Nanocarbons to Create Rich Electroactive Defects toward Simultaneous Sensing Hydroquinone and Catechol. (10th January 2022) - Rao, Qianghai; Hu, Fang Xin; Gan, Li-Yong; Guo, Chunxian; Liu, Yuhang; Zhang, Chunmei; Chen, Chongjun; Yang, Hong Bin; Li, Chang Ming
Abstract: Quantitatively simultaneous detection of hydroquinone (HQ) and catechol (CC) with low limit of detection (LOD) and wide detection range is of critical significance in water quality control but faces great challenges due to their isomer similarity and a large range of contamination concentrations. Herein, high density of boron atoms is introduced into nitrogen-doped nanocarbon (BNC) to realize simultaneous detection of HQ and CC with a large separation of peak potential (Δ Ep ) of 111 mV between oxidations of HQ and CC by differential pulse voltammetry. Besides, extremely low LODs of 33.3 and 16.3 nM for HQ and CC were achieved through amperometric I - t curve with wide linear ranges of 0.099 ∼ 43340 µM and 0.049 ∼ 5110 µM, respectively. The systematical investigation of the enhancement mechanism by spectroscopy and DFT calculations clearly reveal that the boron-nitrogen co-doping creates rich electroactive sites for high sensing performance toward HQ and CC, thereby shedding lights on the great effect of a unique nanostructure on electrocatalysis in sensing applications. Graphical Abstract: Image, graphical abstract